A red pomegranate fruit extract-based formula ameliorates anxiety/depression-like behaviors via enhancing serotonin (5-HT) synthesis in C57BL/6 male mice - Xiping Zhu; Dongxiao Sun-Waterhouse; Chun Cui (Food Science and Human Wellness)
This study investigated the anti-anxiety/anti-depression potential of a formula containing red pomegranate fruit extract (RPFE; 40%, m/m), Lactobacillus rhamnosus (JB-1) (34%, m/m), magnesium gluconate (25%, m/m) and vanillin (1%, m/m). The RPFE formula (dose: 2.0, 1.5 or 1.0 mg/g day) reversed behavioral dysfunctions and body weight gain induced by chronic restraint stress combined with corticosterone injection in C57BL/6 male mice. The RPFE formula exhibited the abilities to normalize the levels of serum inflammatory cytokines (NF-κB, TNF-α, IL-6, IL-1β and IFN-γ) and malondialdehyde (MDA), and activities of superoxide dismutase (SOD), catalase (CAT) and nitric oxide synthase (NOS), as well as relieve the injury of hippocampal neurons. The serotonin (5-HT) levels in hippocampus were increasingly enhanced, which might be mediated by reducing the activity of indoleamine-2,3-dioxygenase (IDO) and increasing the activity of tryptophan hydroxylase (TPH). Thus, the neuroprotective and ameliorating effects on anxiety/depression-like behaviors resulting from the RPFE formula ingestion were possibly related to serotonergic activation, which might be mediated via anti-inflammatory and anti-oxidant actions.